Russia in a Changing World: the Continuity of the Priorities and New Opportunities - V. V. Putin (Vestnik MGIMO-Universiteta)
Speech of the President of the Russia Vladimir Putin at the Meeting of the Russian Ambassadors and Permanent Representatives Abroad at the Ministry for Foreign Affairs of Russia, 9 july 2012.